A matter of time? Gender equality in the teaching profession through a cross-national comparative lens. Issue 6 (17th August 2020) - Moreau, Marie-Pierre
ABSTRACT: This article draws primarily on a dataset of 60 semi-structured interviews conducted with teachers working in English and French state-funded secondary schools. Informed by feminist sociological theories of work and education and a cross-national comparative perspective, it explores the mechanisms leading to the production of gender inequalities in a profession which is often thought of as egalitarian or even favourable to women: teaching. A multi-level approach is adopted, which considers how the macro-social, meso-social and micro-social dimensions of the social world interact with each other and lead to the production of context-specific gender patterns, with specific attention to the effects of the spatio-temporal regimes of teaching which prevail in each country.